2015
DOI: 10.1038/srep16568
|View full text |Cite
|
Sign up to set email alerts
|

Optimally conductive networks in randomly dispersed CNT:graphene hybrids

Abstract: A predictive model is proposed that quantitatively describes the synergistic behavior of the electrical conductivities of CNTs and graphene in CNT:graphene hybrids. The number of CNT-to-CNT, graphene-to-graphene, and graphene-to-CNT contacts is calculated assuming a random distribution of CNTs and graphene particles in the hybrids and using an orientation density function. Calculations reveal that the total number of contacts reaches a maximum at a specific composition and depends on the particle sizes of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…Poor electrical conductivity of polymers is another problem, which limits the use of polymer composites in many applications. It is observed that the use of well dispersed network of CNTs with high electrical conductivity improves electrical properties of the nanocomposite in which they are added. The effect on electrical conductivity of PDMS after addition of vertically aligned carbon nanotubes is investigated next.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor electrical conductivity of polymers is another problem, which limits the use of polymer composites in many applications. It is observed that the use of well dispersed network of CNTs with high electrical conductivity improves electrical properties of the nanocomposite in which they are added. The effect on electrical conductivity of PDMS after addition of vertically aligned carbon nanotubes is investigated next.…”
Section: Resultsmentioning
confidence: 99%
“…The conductivity of CNT‐based nanocomposites is viewed as a combined effect of the conductivity of the filler as well as that of interphase region surrounding the VACNTs . Consequently, their addition in otherwise insulating PDMS provides a conducting path and leads to the observed improvement in electrical conductivity of pure PDMS. With the reduction of sheet resistance (0.08 KΩ/sq), PDMS‐VACNT array finds huge applications in the flexible‐stretchable electronics, energy storage devices, flexible strain sensor, flexible pressure sensors, stretchable circuits, flexible displays, and electronic skins .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, hybridizing multiple conductive materials improves conductivity compared to that of a single conductive material. For example, it has been confirmed that a specific proportion of CNT:graphene hybrid material has a higher conductivity than a 100% CNT or graphene material [116].…”
Section: Hybrid Materialsmentioning
confidence: 92%
“…11). The hybrid buckypapers showed the highest electrical conductivity at a volume ratio (9:1) of Pw-MWCNT and Pw-G, demonstrating that the randomly dispersed MWCNTs and the graphene together provide a synergistic effect by increasing the conducting network [35].…”
Section: Characteristics Of Pw-mwcnts and Pw-gmentioning
confidence: 96%